High‐throughput formation of miniaturized cocultures of 2D cell monolayers and 3D cell spheroids using droplet microarray. Issue 1 (2nd December 2022) - Cui, Haijun; Tronser, Tina; Wang, Xianxian; Wesslowski, Janine; Davidson, Gary; Popova, Anna A.; Levkin, Pavel A.
Abstract: Most of the biological processes, including cell signaling, cancer invasion, embryogenesis, or neural development, are dependent on and guided by the complex architecture and composition of cellular microenvironments. Mimicking such microenvironments in cell coculture models is crucial for fundamental and applied biology investigations. The ability to combine different cell types grown as both two‐dimensional (2D) monolayers and three‐dimensional (3D) spheroids in specific defined location inside a microculture environments is a key towards in vitro tissue modeling and towards mimicking complex in vivo cellular processes. In this study, we introduce and investigate a method to create in vitro models of 2D cell monolayers cocultured with 3D spheroids in defined preorganization. We demonstrate the possibility of creating such complex cellular microenvironments in a high‐throughput and automated manner by creating arrays of such droplets containing prearranged 2D and 3D cellular microcolonies. Furthermore, we demonstrate an application of this approach to study paracrine propagation of Wnt signaling between 2D and 3D cellular colonies. This method provides a general approach for the miniaturized, high‐throughput, and automated formation of complex coculture cellular microarchitectures that will be useful for mimicking various in vivo complex cellular structures and for studying complex biological processes in vitro. Abstract : A programmable droplet merging method is demonstrated to create in vitro models of two‐dimensional (2D) cell monolayers cocultured with three‐dimensional (3D) spheroids in defined preorganization. Benefiting from the independence of this 2D and 3D structure, we demonstrate an application of this approach to study paracrine propagation of Wnt signaling between 2D and 3D cellular colonies.